Patient safety incidents involving sick children in primary care in England and Wales: a mixed methods analysis - Rees, Philippa; Edwards, Adrian; Powell, Colin; Hibbert, Peter; Williams, Huw; Makeham, Meredith; Carter, Ben; Luff, Donna; Parry, Gareth; Avery, Anthony; Sheikh, Aziz; Donaldson, Liam; et al. (Public Library of Science, 2017)
Background: The UK performs poorly relative to other economically developed countries on numerous indicators of care quality for children. The contribution of iatrogenic harm to these outcomes is unclear. As primary care is the first point of healthcare contact for most children, we sought to investigate the safety of care provided to children in this setting.